Proceedings of the 1st Borobudur International Symposium on Humanities, Economics and Social Sciences (BIS-HESS 2019) 2020
DOI: 10.2991/assehr.k.200529.098
|View full text |Cite
|
Sign up to set email alerts
|

Ziswaf Collection Strategy on LAZISMU X, Indonesia

Abstract: The concept of zakat is recommended to create a balance of individual and social life. The collection of zakat in LAZISMU X is still slightly contrary to its enormous potential. This study aims 1) To find out the of zakat's fund collection method on LAZISMU X 2) To find out the application of business strategies in the form of Business Models Canvas in collecting zakat at LAZISMU X. This study used a descriptive qualitative approach. The collected data included primary data and secondary data by observations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The effect of ICT in zakat management has been investigated, indicating its significant and positive effect on good governance (Yolanda et al, 2020). Hakim et al (2020) proposed the use of digital technology for zakat collection. They reported that the collection of zakat conducted by most zakat institutions is still conventional; thus, digitising zakat management, including the collection of zakat, infaq, alms and waqf (ZISWAF), was proposed to increase the effectiveness of zakat collection.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of ICT in zakat management has been investigated, indicating its significant and positive effect on good governance (Yolanda et al, 2020). Hakim et al (2020) proposed the use of digital technology for zakat collection. They reported that the collection of zakat conducted by most zakat institutions is still conventional; thus, digitising zakat management, including the collection of zakat, infaq, alms and waqf (ZISWAF), was proposed to increase the effectiveness of zakat collection.…”
Section: Introductionmentioning
confidence: 99%
“…And be steadfast in prayer; practice regular charity; and bow down your heads with those who bow down [in worship]. 15 In another verse, Allah (SWT) said:…”
Section: Obligation Of Zakahmentioning
confidence: 99%
“…In addition, research conducted by [6] found that ZIS management at BAZNAS (Badan Amil Zakat Nasional) in Bali during the pandemic had followed Covid-19 protocol, such as the use of masks and physical distancing when meeting with muzakki (a Muslim or business entity that is obliged to pay zakat). Another study conducted by [7] obtained the results that Lazismu X has implemented three principles of management strategies such as ZIS digitization, utilization of social media, and amil resources. Some of the studies above have presented different results, but this research focuses on door-to-door services which have not been carried out in previous studies.…”
Section: Introductionmentioning
confidence: 99%